Assessment of factors determining an HbA1c concentration ≤7.5% in patients with type 1 diabetes: 评估决定1型糖尿病患者HbA1c≤7.5%的因素. Issue 2 (28th June 2017) - Yamada, Eijiro; Okada, Shuichi; Nakajima, Yasuyo; Bastie, Claire; Tagaya, Yuko; Osaki, Aya; Shimoda, Yoko; Shibusawa, Ryo; Saito, Tsugumichi; Ozawa, Atsushi; Yamada, Masanobu
Abstract: Background: Establishing an optimal insulin regimen is crucial for maintaining glycemic control in patients with type 1 diabetes (T1D). The aim of the present study was to determine the insulin dose required to achieve an HbA1c concentration ≤7.5% in Japanese patients with T1D. Methods: The present multicenter cross‐sectional study was performed at three institutes in Japan. Information was collected regarding patient age, sex, body weight, body mass index (BMI), HbA1c, total daily insulin dose (TDD), and total basal insulin dose (TBD), and the effects of these factors on achieving HbA1c ≤7.5% were investigated. Results: Of 107 patients with T1D, 92 had no detectable endogenous insulin secretion: 39 had HbA1c ≤7.5% (well‐controlled group) and 53 had HbA1c >7.5% (poorly controlled group). No significant differences in age, sex, height, body weight, BMI, diabetes duration, stage of diabetic kidney disease, treatment, or TDD were noted between the poorly and well‐controlled groups. The TBD as a percentage of TDD (%TBD) was lower in patients with well‐controlled diabetes ( P < 0.05) after adjustment for age, gender, and diabetes duration. In the well‐controlled group, TDD was correlated with body weight ( R = 0.51), BMI ( R = 0.44), body surface area ( R = 0.41), and TBD ( R = 0.73; P < 0.01 for all), but TBD was not correlated with BMI or body surface area. In our population, a %TBD of approximately 30% was appropriate, without considering BMI. Conclusions: To achieve HbA1c ≤7.5 in patients with T1D, TDD should be calculated based on body weight, and the %TBD should be set at 30% in the Japanese population. Abstract : Highlights Appropriate insulin dose required for maintaining good glycemic control were assessed in patients with type 1 diabetes. Glycemic control did not depend on the total daily insulin dose; rather, the ratio of basal:  bolus insulin is important. To achieve an HbA1c concentration ≤7.5%, the total daily insulin dose (TDD) should be based on body weight, and the total basal insulin dose as a percentage of TDD should be set at 30% in the Japanese population.